Pengaruh Media Video Animasi Berbasis Web Terhadap Hasil Belajar IPS Siswa Kelas IV SD - Alfionita, Marinda; Erdiana, Lita; Nurhayati, Eni (Universitas Negeri Makassar, 2024)
The purpose of this study was to determine the effect of web-based animated video media on learning activities and social studies learning outcomes of grade IV students at SDN Keboguyang which was taken from several problems that existed in the school. This type of research is quasi-experimental with nonequivalent control group design. Using non-probability sampling technique, namely Saturated Sampling consisting of class IV A and IV B students at SDN Keboguyang. The results of the analysis show that web animation video media has a significant positive impact on learning activities and student social studies learning outcomes at the school. The evaluation of student activity in the experimental class showed an average of 92.11% with the Very Active category. On the other hand, students in the control class showed an average result of 85.47% with the Active category. The use of web-based animated videos has a significant impact on the social studies learning outcomes of grade IV elementary school students.